The Question of Identity in the Anglophone Literatures of the Arab and Indian Diasporas in Australia - CHAKOUR KHAOULA (Faculté des Lettres et Sciences Humaines, Béni Mellal - Doctorat ou Doctorat National, 2022)
This thesis explores the various patterns of identity which crystallize in the writings of Arab-Australian and Indian-Australian authors. In fact, it principally intends to demonstrate that the process of identity formation in the Australian diasporic context is a heterogeneous experience which involves a myriad of dynamics. To fulfill its aim, this dissertation is predicated on the analysis of literary works by Arab-Australian and Indian-Australian authors, namely Randa Abdel-Fattah, Samah Sabawi, Chafic Ataya, Cecile Yazbek, Rashma Kalsie, Roanna Gonsalves, Kavita Ivy Nandan, Rashida Murphy, and Suneeta Peres da Costa. The choice of these two literary venues to be the core of analysis emanates from the academic marginalization to which both have been subjected despite their creative literary perspectives. Thus, the thesis is an attempt to fill this void in diaspora literature and to bring to light these sidelined literary realms. Through its recourse to the comparison of these two literatures and the interdisciplinary implementation of a variety of concepts, including exile, nation, space, history, memory, hybridity, culture, and transculture, it evinces that there are three paradigms of identity underlying both Arab-Australian and Indian-Australian literatures: exilic identity, diasporic identity, and transcultural identity. Exilic identity emerges as a form of anchoring resistance to the variegated manifestations of exile. It hinges on a close identification with space and nation in the Arab-Australian works and with nostalgia, culture, and religion in the Indian-Australian literature. Furthermore, the fluidity of identity is typified in the mutable forms which diasporic identity assumes. These incorporate a classical, bipolar model centered on the cultural, social, and racial configurations outlined by the dyad homeland/hostland, a contemporary pattern built on the concept of diaspora consciousness, and a triadic mode which crisscrosses various temporal, spatial, and cultural contexts. The thesis also unveils that the studied literature is a site where transcultural identity surfaces. The latter is a nascent paradigm of identity which entails the nullification of hegemonic centers and the fusion of cultures. The articulation of these identity patterns in Arab-Australian and Indian-Australian literatures uncovers many similarities and differences between the two. Yet, there is no doubt that the comparison of both literatures reveals the dynamic, complex, and open-ended nature of the examined identities. It is the pluralistic nature of identity highlighted in this dissertation that may open future research prospects to further explore the marginalized Arab-Australian and Indian-Australian literature and to tackle the vexed questions which rise from the reflections on identity incorporated here.
Keywords: identity; exile; nation; space; nostalgia; culture; religion; diaspora; memory; history; hybridity; transculture; transcultural continuum; feminism; anti/post -colonialism; Littérature; Études Postcoloniales